2022
DOI: 10.3892/mco.2022.2517
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP25 expression in colorectal cancer as a biomarker associated with favorable prognosis

Abstract: Although progress has been made in the early diagnosis of colorectal cancer (CRC) and in the systemic therapy of patients with CRC, the prognosis for advanced CRC remains poor. Our previous study demonstrated that ARHGAP25 overexpression significantly inhibits CRC cell growth, invasion and migration. However, it was not possible to evaluate and analyze the overall survival (OS) rate of patients with CRC. Thus, the discovery of relevant factors and their expression on the basis of existing research is necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The invasion capability of alveolar rhabdomyosarcoma cells is controlled by the RhoE/ROCK/ARHGAP25 signaling pathway [ 12 ]. Furthermore, researchers discovered that ARHGAP25 was downregulated in colorectal cancer (CRC) and that upregulating ARHGAP25 decreased CRC metastasis both in vivo and externally [ 16 ]. One study revealed that the abnormal expression of ARHGAP25 reduces lung cancer cell proliferation and migration [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The invasion capability of alveolar rhabdomyosarcoma cells is controlled by the RhoE/ROCK/ARHGAP25 signaling pathway [ 12 ]. Furthermore, researchers discovered that ARHGAP25 was downregulated in colorectal cancer (CRC) and that upregulating ARHGAP25 decreased CRC metastasis both in vivo and externally [ 16 ]. One study revealed that the abnormal expression of ARHGAP25 reduces lung cancer cell proliferation and migration [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thuault et al revealed for the first time that ARHGAP25 inhibits the invasion of alveolar rhabdomyosarcoma (ARMS) cells [ 12 ]. Previous studies have shown that ARHGAP25 overexpression significantly inhibits the growth of many neoplastic cells and suppresses their migration and invasion [ 13 16 ]. However, the association between ARHGAP25 and VM in NSCLC has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, its specific role in osteosarcoma is still unclear, so we can conduct further research. ARHGAP25 has also been widely studied as a tumor suppressor gene in cancer, including Pancreatic adenocarcinoma (PAAD), NSCLC, Lung cancer, and CRC [ 14 , 42 46 ]. Epithelial-mesenchymal transition (EMT) is a common mechanism of tumor metastasis, which can reduce the adhesion between cells so that tumor cells can be separated from the original site to metastasize [ 47 ].…”
Section: Discussionmentioning
confidence: 99%